A fully distributed control scheme for power balancing in distribution networks. Issue 2 (2020) - Bella, Alessio La; Bonassi, Fabio; Klaus, Pascal; Scattolini, Riccardo
Abstract: The progressive diffusion of generation units based on intermittent renewable energy sources, as well as the increasing volatile power demand, calls for a new framework to compensate the power variability in a local fashion. In this context, the European Union instituted the figure of the Balance Responsible Party, i.e. an entity entitled of internally compensating the power uctuations, exploiting a portfolio of local dispatchable units. Considering a distribution network carrying balance responsibility, this work devises a scalable, fully distributed, multilayer control strategy for internal power balancing. The proposed scheme features multiple local MPC regulators, performing an autonomous power balancing; a supervisory layer based on Distributed Consensus ADMM is introduced to coordinate local regulators when some of them exhausts its local resources. Numerical results eventually show the effectiveness of the approach